Engineering bio-inert and thermostable poly(vinylidene difluoride) membranes by grafting thermal-tolerant copolymers via ring-opening reaction - Irish Valerie Maggay; Ying-Tzu Chiu; Hao-Tung Lin; Antoine Venault; Yung Chang (Journal of Membrane Science Letters)
This study explores the development of a thermostable and bio-inert PVDF membrane by grafting poly(acrylamide-r-N-vinylpyrrolidone) (P(AA-r-NVP)) onto a styrene-co-maleic anhydride (SMA)-functionalized PVDF substrate. The fabrication process involved blending SMA into the PVDF matrix followed by vapor-induced phase separation process to form the porous membrane. P(AA-r-NVP) was then grafted onto the membrane through the ring-opening of maleic anhydride groups. Characterization through ATR-FTIR and XPS confirmed successful surface modification. Antifouling performance of the membranes were assessed through bacterial adhesion tests before and after steam sterilization. Before sterilization, SMA3_A3V7 effectively resisted up to 97 % of E. coli adhesion. After steam sterilization, SMA3_A3V7 demonstrated excellent thermal stability, with a minimal 1.25 % increase in bacterial adhesion, compared to a 250 % increase in the unmodified PVDF membrane. These findings feature the effectiveness of utilizing SMA in simplifying the grafting process and the contribution of the thermostable and bio-inert polymer in imparting high-temperature resistance and antifouling resistance to the membrane, enabling versatile applications.